Infection with colonization factor antigen I-expressing enterotoxigenic Escherichia coli boosts antibody responses against heterologous colonization factors in primed subjects - RUDIN, A.; WIKLUND, G.; WENNERÅS, C.; QADRI, F. (Epidemiology and infection, 1997)
Enterotoxigenic Escherichia coli (ETEC) adhere to the intestinal mucosa by a number of fimbrial colonization factors (CFs) that have been claimed to induce only type-specific immunity. However, adult Bangladeshi patients infected with CFA/I-expressing bacteria, developed significant plasma IgA antibody responses, as determined by enzyme-linked immunosorbent assay, not only against the homologous fimbriae but also against several heterologous CFs, i.e. CS1, CS2, CS4 and PCFO166 fimbriae. In contrast, North American volunteers, who had probably not been infected by ETEC previously, responded with serum IgA against CFA/I fimbriae but not against any other CFs after symptomatic infection with CFA/I-expressing ETEC. Thus, infection with CFA/I-expressing bacteria may boost immune responses against CFs with a related amino acid sequence in previously primed subjects.